Perencanaan Jalur Kereta Api Lintas Kamal-Suramadu Dengan Global Mapper dan Autocad Civil 3dD (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2023)
The development of the railway network in Madura is in the form of reactivation of old lines and construction of new lines, as stated in the National Railway Master Plan (RIPNas) and Indonesia Presidential Decree No. 2128 Year 2018. This research will focus on planning the reactivation of the Kamal-Bangkalan-Suramadu railway line, with the aim of encouraging the development of railways on Madura Island, which can improve the economy and mobility of the Madurese people. The Kamal-Suramadu railway planning will refer to Minister of Transport Regulation no. 11 2012 and Minister of Transport Regulation no. 60 2012, and by using Global Mapper and Civil 3D software. Most of the existing railway line in Bangkalan-Kamal has been used as a densely populated settlement or government (54%), medium density settlement (24%), and paddy fields or vacant land (22%). The existing railway line uses a single track with a spoor width of 1067mm and R25 type rail. The selected trace is alternative trace number 2 with a length of 31,152 metres and requires 566,266 m2 of land for its construction. Horizontal alignment planning resulted in 7 horizontal curves with a radius of 1100 m (curves 1, 2, and 7), 800 m (curves 3 and 5), and 950 m (curves 4 and 6). Cumulative cut volume of 2,399,262.85 m3, and cumulative fill volume of 891,563.7 m3. Railway components required include 51,921 pieces of concrete sleepers, 207,684 pieces of pendroller fastening, 2,493 pieces of R54 rail, 48,286 m3 ballast, and 59,812 m3 subballast